N-Aminations of Benzylamines and Alicyclic Amines with Nitrosoarenes to Hydrazones and Hydrazides - Purkait, Anisha; Jana, Chandan K. (Synthesis, 2019)
Unlike other alkylamines, benzylamines upon reaction with a nitrosoarene undergo oxidation to the corresponding imines. A direct amination of benzylamines, which was difficult to achieve due to its facile oxidation, to the corresponding hydrazones is reported. A wide variety of benzylamines and N-heterocycles were reacted with nitrosoarenes to provide structurally diverse hydrazones and hydrazides, respectively. Moreover, the direct N-amination reaction was applied to the one-pot synthesis of triazoles.
Keywords: N-amination; hydrazones; nitrosoarenes; triazoles; benzylamines